A Study of Smart Healthcare Service Model Based on Cloud Platform: Focus on Small and Medium Sized Hospitals (Medico Legal Update, 2019)
The objective is to propose a cloud hospital information system (cHIS) to allow small and medium sizedhospitals to provide smart healthcare services and gain improved competitiveness. The research wasconducted on cloud platform-based HIS service, mobile electronic medical record (EMR) service, personalbiological record (PBR) service and healthcare big data service. Cloud computing technology was usedfor the HIS service to minimize the operating cost, IoT was applied to the mobile EMR and PBR services,and big data technology was used for the healthcare big data service to raise the efficiency in the clinicalsetting. This study examined the measures for promoting the use of cloud computing technology in thehealthcare sector. If service providers can provide affordable, high-quality cloud healthcare services, suchservices will become high in demand despite hindrances. Thus, the architecture and service model of thecHIS were designed to minimize the operating costs through resource pooling achieved by virtualizing thehardware and application programs to promote affordability. Also, CloudSim was used to assess the stabilityand efficiency in relation to the data access time, service processing time and service wait time. First, theresults of the experiment showed that an increase in the cloud storage disk and network bandwidths allowsmore users to be serviced. Second, it was found that the packet size had little to no impact on the systemperformance. Third, it was found that cloud-based distributed storage and processing was more efficientthan using a web-based database in case of processing large amounts of data. The system presents economicadvantages including maximized sharing of resources and minimized costs, enables real-time exchange ofhealthcare data, and promotes the use of collective intelligence for better healthcare services.